2019
DOI: 10.1038/s41598-019-54245-4
|View full text |Cite
|
Sign up to set email alerts
|

Identification of potential molecular pathogenesis mechanisms modulated by microRNAs in patients with Intestinal Neuronal Dysplasia type B

Abstract: This study proposed to determine global microRNA (miRNA) expression and miRNA-regulated pathways in Intestinal Neuronal Dysplasia type B (IND-B). Fifty patients (0–15 years old) with IND-B were included in the study. Peripheral blood samples were collected from all 50 patients and from 10 healthy asymptomatic children (controls). Rectal biopsies were collected from 29/50 patients; biopsy tissues were needle microdissected to isolate the different intestinal layers, for molecular analysis. Global miRNA expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Obtaining intestinal samples for use as controls has ethical limitations because of the need for invasive procedures to obtain tissue samples. In some studies, the control group was composed of intestinal samples from patients with congenital intestinal malformations such as anorectal abnormalities, which cannot be considered healthy controls[ 41 ]. In addition, the variation in the number of ganglion cells related to age, especially during the first year of life, leads to the need for age-matched controls, making it difficult to develop an appropriate control group[ 26 ].…”
Section: Lack Of Diagnostic Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Obtaining intestinal samples for use as controls has ethical limitations because of the need for invasive procedures to obtain tissue samples. In some studies, the control group was composed of intestinal samples from patients with congenital intestinal malformations such as anorectal abnormalities, which cannot be considered healthy controls[ 41 ]. In addition, the variation in the number of ganglion cells related to age, especially during the first year of life, leads to the need for age-matched controls, making it difficult to develop an appropriate control group[ 26 ].…”
Section: Lack Of Diagnostic Criteriamentioning
confidence: 99%
“…Recent studies have shown that IND-B can originate from genetic alterations, which directly influence the embryological development of tissues derived from the neural crest. Angelini et al [ 41 ] showed significantly unregulated expression of microRNAs in the submucosal and muscular layers of the colon and peripheral blood of patients with IND-B. The molecular pathways biologically regulated by these microRNAs (axon guidance, nerve growth factor signaling, neural cell adhesion molecule (NCAM) signaling for neurite outgrowth, neuronal system, and apoptosis) show activities related to the ENS and, therefore, can be related to the pathogenesis of IND-B.…”
Section: Uncertainties and Recent Advancesmentioning
confidence: 99%